Initial evaluation of a brief pharmacy-led intervention to modify beliefs about medicines and facilitate adherence among patients hospitalised with acute coronary syndrome. Issue 1 (13th December 2019) - Crawshaw, Jacob; Weinman, John; McRobbie, Duncan; Auyeung, Vivian
Abstract : Objectives: Medication non-adherence is common among patients with acute coronary syndrome (ACS) and is associated with poor clinical outcomes. To date, pharmacists have been underutilised in the delivery of adherence interventions. Across two studies, we assessed the feasibility, acceptability and effectiveness of a novel pharmacy-led intervention for patients hospitalised with ACS. Methods: The theory-based intervention was comprised of two personalised sessions addressing perceptual (negative/erroneous treatment beliefs) and practical (suboptimal action planning) barriers to adherence. Study 1: A single-arm, feasibility and acceptability study was conducted to determine proof-of-concept. Pre–post-comparisons using the Beliefs about Medicines Questionnaire-Specific (BMQ-S) were made. Study 2: A non-randomised controlled before–after pilot study was conducted with the intervention delivered by a team of clinical pharmacists. Follow-up data were collected at 6 and 12 weeks post-discharge. Primary outcome measures included the BMQ-S and the Medication Adherence Report Scale 5. Results: Study 1: 15 patients received the intervention and reported higher BMQ-S necessity scores post-intervention. The intervention was deemed highly acceptable to patients; therefore, further testing was sought. Study 2: A total of 56 patients were recruited: control (n=29) versus treatment (n=27). At 6-week follow-up, the treatment group had higher BMQ-S necessity scores (M=21.8, SD=3.1) compared with control (M=19.8, SD=2.7; p=0.045), although this effect was not maintained at 12 weeks. No differences were reported in the other outcome measures. Conclusions: Although the intervention was acceptable to patients, poor fidelity in delivery raises questions about its feasibility in practice. Furthermore, there was some impact on patients' beliefs about medications but no effect on adherence. These findings demonstrate the importance of conducting feasibility and acceptability studies when developing adherence innovations in clinical care. Future studies should consider enhancing the training process to ameliorate fidelity issues.